A pH-responsive phosphoprotein washing fluid for the removal of phenanthrene from contaminated peat moss in the cold region. (February 2023) - Yue, Rengyu; An, Chunjiang; Ye, Zhibin; Li, Xixi; Li, Qing; Zhang, Peng; Qu, Zhaonian; Wan, Shuyan
Abstract: Oil pollution is one of the major environmental concerns in the petroleum industry. In this study, a cheap food-grade sodium caseinate (NaCas) was used as a pH-responsive washing fluid in the remediation of phenanthrene (PHE) affected peat moss. The effects of environmental factors on the removal of PHE were systematically investigated. The results showed that increasing NaCas concentration and washing temperature improved the PHE mobilization, while high salinity and humic acid dosage displayed a negative effect. The factorial analysis revealed that three individual factors and two interactions exhibited significant effects on the washing performance. Due to the pH-responsive property of NaCas, the turbidity, total organic carbon (TOC), and chemical oxygen demand (COD) of the washing effluent were remarkably reduced by simply adjusting the solution acidity, improving the practical application of such a washing method. Significantly, the toxicity modeling proved that NaCas can reduce the binding energy between PHE and superoxide dismutase (SOD) of the selected marine organism, and thus relieve the toxicity of PHE to the organisms. Given these advantages, NaCas-assisted washing can be a viable option for the remediation of contaminated peat moss. Graphical abstract: Image 1 Highlights: Sodium caseinate (NaCas) was used for peat moss decontamination in the cold region. NaCas washing fluid showed good PHE immobilization. PHE removal efficiencies were affected by different conditions. Washing effluent could be readily treated through pH-responsive separation. Toxicity modeling analysis shows that NaCas could reduce the biotoxicity of PHE to organisms.